PENGARUH KOMPETENSI GURU TERHADAP KINERJA GURU SMPN I LAMBUYA KAB. KONAWE MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Heriswanto Heriswanto (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
Influence on Performance Competence Master Teacher At SMPN I Lambuya Konawe Through Work Motivation As an intervening variable. The purpose of this study is to describe and test the effect of teacher competence on motivation and performance of teachers. Specifically the purpose of research to explain and examine the role of teachers' motivation to work in mediating the relationship between the competence of the teacher's performance. The design of this research uses explanatory research approach with data collection conducted cross-section through the questionnaire. The population of this study was all government school teachers in SMP Negeri 1 Lambuya Konawe totaling 45 people. The sampling technique is saturated samples (census) in which the entire population as a sample of 45 teachers. Data analysis techniques to answer the problem in this research hypothesis is Partial Least Square (PLS). The results showed that teacher competence and significant positive effect on work motivation and performance of teachers. Furthermore, teachers work motivation positive and significant impact on teacher performance. Keywords: Teachers Competency, Motivation Work, Teacher Performance